prototype infrastructure for the secure aggregation of imaging and pathology data for colorectal cancer care (2006)
In recent years, a significant number of developments across a broad range of disciplines have allowed researchers and clinicians to start to build up a picture of cancer development. In this paper we report upon the development of a prototype of a secure distributed infrastructure that links imaging data from pathology and radiology. The intention is that a fully-developed system will be capable of supporting studies that will examine whether prognostic and diagnostic features which are apparent in histopathological sections and clinical scans are related. Further these studies will consider whether these features can be meaningfully linked i